Towards an Ethics for the Healthcare Metaverse - Tretter, Max; Samhammer, David; Ott, Tabea; Dabrock, Peter (Journal of Metaverse, 2023)
Harnessing the metaverse for medical and healthcare purposes is currently heralded as the “next frontier in healthcare.” However, to ensure the “amazing possibilities” of the so-called “healthcare metaverse” can be fully realized, it’s vital to proactively identify and address potential challenges, especially those of an ethical nature. This paper aims to spotlight these ethical challenges within the healthcare metaverse and chart a course for confronting these issues and cultivating an ethics framework for this emerging field. We will demonstrate that the ethical quandaries within the healthcare metaverse bear striking similarities to those seen in digital medicine, an arena that grapples with vast quantities of data and the application of artificial intelligence. Reflecting on these parallels, we explore how six central ethical challenges in digital medicine – 1) accessibility, 2) fairness, 3) discrimination and bias, 4) responsibility, 5) privacy, data safety and security, and data ownership, as well as 6) environmental issues – unfold within the healthcare metaverse’s virtual boundaries and show that the metaverse’s immersive nature further intensifies these ethical challenges. In view of this, we advocate that the next phase in forging ethics for the healthcare metaverse involves a nuanced reconsideration of current ethical methods and principles in digital medicine, with an emphasis on the immersive element of the metaverse. We foresee the concept of embodiment within virtual settings to be at the heart of this immersion-focused reassessment.
Keywords: Virtual Reality; Medicine; Bioethics; Challenges; Medical Ethics; Artificial Intelligence